Peculiarities of psychomotor reaction of handball players - Muckus, K.; Skarbalius, A. (Education. Physical training. Sport, 2000)
The aim of the research was to examine the psychomotor reaction (PMR) of the Lithuanian juniors' handball team and to determine which kinematic and dynamic indices of the jump are responsible for the formation of the separate components of the PMR. In July 1999 the study of 14 members of the Lithuanian juniors' handball national team was carried out. The arithmetical mean of the height of the subjects was 187.3±3.87 cm and that of the weight 77.1±7.62 kg respectively. The following two tests were performed: 1) squat jump and 2) research in the PMR. Test 1 was aimed at determining the strength of the athletes and physical properties that accompany associated with it. Test 2 was aimed at establishing the elements of the PMR. In both cases the force of the plant reaction (dynamogram) during the high jump was registered. Making use of the dynamogram obtained the kinematic and dynamic indices were calculated. It has been established that the values of the phase duration of squating take-off and flight as well as those of depth of squating and speed at the moment of breaking away from touch with the platform, also the values of the high jump and the work performed during the maximal jumps were reliably greater than during the fast jump. Meanwhile both the average strength and dynamic strength were greater during the fast jump. The power values in the case of both jumps were alike. The correlation between the speed of the jump was also examined. It has been established that there exists a strong positive correlation between the overall time of the PMR, the duration of the squating phase (r=0.91), the depth of the squating (r=0.83) and the relative power (r=0.64). There is also a good correlation between the latent time of the reaction, the duration of the squating phase (r=0.69) and the depth of the squating (r=0.64). The time of the movement is most strongly dependent on the parameters of the jump. There exists a strong positive correlation between the time of the movement, the duration of the squating phase (r=0.61), the speed of breaking away from touch with the platform (r=0.76), the depth of the squating (r=0.82), the height of the jump (r=0.75) and the relative power (r=0.68). There exists a negative correlation with the dynamic force (r=-0,62). We have also examined in what way the PMR indices of handballers were dependent on the position of the players in the court. We have found out that all PMR indices of the players of the 2nd line were reliably (p<0.05) smaller than the respective indices of the players of the 1st line. The latent reaction time of the goalkeepers is the longest although the time of the movement is similar to that of the 2nd line players. There was a statistically insignificant difference in the values of kinematic and dynamic indices of the jump between the players of different lines. Body mass and height of the players had no influence whatever on the PMR and jump indices. On the basis of the research carried out we have made the following conclusions: 1) The kinematic and dynamic indices of the squat jump are dependent on motivation: the duration of the maximal jump, average force and the work performed are greater in the case of the maximal jump whereas greater dynamic force is developed when performing the fast jump; 2)The time of psychomotor reaction depends on the duration of the jump and the dynamic force; 3) Handball players of the 2nd line distinguish themselves by the fastest reaction whereas the reaction of goalkeepers and 1st line players is slower.